ROLE OF HUMAN RESOURCE MANAGEMENT FUNCTION ( PLANNING, ORGANIZING, ACTUATING, CONTROLLING,) SUPPORT SERVICES FOR VISITORS IN LIBRARY (STUDY IN NATIONAL LIBRARY UPT BUNG KARNO BLITAR EAST JAVA) - Puji Choirul Ana (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This research method is study aims to determine the human resource function and also to determine the quality of visitor services at the National Library Unit Blitar Bung Karno . among other functions is of planning, organizing, directing and monitoring .. while the technical function or opeatif tablespoons of management is the recruitment, procurement, development / education and training, compensation or remuneration, integration, maintenance and retirement. Research using qualitative descriptive methods. data collection by interview, observation and documentation. The sample is all library staff totaling 56 people. interviews were conducted with sources / informants who know the ins and outs of tablespoons in the library. when research started in February 2016 to 9 June 2016 (4 months). Results of the research is the application of the management function has been as expected, but the function of planning and supervision of more handled by the central library. While organizing and directing has been carried out by the head of the library in accordance with management functions. While the service perceived by the visitors is quite qualified